Global Challenge of Health Communication: Infodemia in the Coronavirus Disease (COVID-19) Pandemic - Hamid Allahverdipour (Hamadan University of Medical Sciences, 2020)
Dear Editor The international community has been faced with one of the most critical health conditions in recent decades due to the Coronavirus disease (COVID-19) pandemic which experience hundreds of thousands of infected cases and tens of thousands of deaths. Alongside of COVID-19 pandemic we have been faced a new phenomenon of "Infodemic" or "epidemic of false information" about COVID-19. Currently, a huge of unverified information is being disseminated about various aspects of COVID-19 disease, the methods of control and prevention of disease, and about its consequences through social media, television networks, and news agencies. In this regard, the Director General of the World Health Organization (WHO), Mr Tedros, at the Munich Security Conference on February 15, stated that '' We are not just fighting the COVID-19 epidemic,concurrently, we are also struggling with an "infodemic" which it can be a serious problem [1]. In other words, false information is rapidly circulating on social media, and countering fake news is likely to continue as long as the coronavirus spreading. As a result, the WHO is working with social media such as Twitter, Facebook, Tencent, Pinterest, and TikTok to publish the verified news about COVID-19 [2]. To provide verified accurate information, after announcing of COVID-19's outbreak by China's Public Health Emergency Department, the World Health Organization amid to develop and build a series of mechanisms as a new information platform which it is called "WHO Information Network for Epidemics (EPI-WIN)", to share accurate information to specific target groups. Despite the WHO's efforts to control coronavirus, the international community is now witnessing numerous unverified news about COVID-19 that have led to a global confusion [1]. So that, WHO's Director of Infectious Diseases, Sylvie Briand stated that "we know that with the spread of any disease, a tsunami of information dissemination occurs and in this published information, there is always false and rumors information [2]. The information tsunami phenomenon has existed even in the Middle Ages, but the difference between the present and the past is another phenomenon which we know it as "social media". Social media is like viruses that travel with people and move even faster and further, which is itself a new challenge, which can have adverse effects alongside the consequences of the COVID-19 epidemic [1]. As Alexandra Kozmanovic, director of social media at WHO Communications, stated "Combating infodemia and the spread of inaccurate information is a common effort between the WHO's Risk Communications Division and the EPI-WIN platform to produce and disseminate verified information about COID-19. For this reason, as soon as some questions or rumors information are circulated, the WHO's Communications Division seeks to prevent gossip and inaccurate information by finding evidence-based answers and contributing to transparency and accurate information. This seems it's a role that the Bureau of Health Education of the Iranian Ministry of Health must be taken this responsibility. In fact, after the COVID-19 epidemic in China, misleading rumors and false theories about the origin of coronavirus, ways of transmission, methods of controlling and treatment of active cases came up, which was lead to outcomes such as being worried and nervous, shopping and food storage, all of which reflect the impact of a new information ecosystem called "Infodemia" that is a 21st century feature of social media [3]. This crisis is characterized by the simultaneous spread of the virus and the relevant information. In other words, not only the virus is spreading very fast, but also false information about the outbreak of the disease also spread rapidly and as a result of the panic it caused among people. It seems, social media is moving faster than the spread of COVID-19 [3]. However, in Iran, some people, without being worried about this disease, do not attempt to protect him/herself and others. It is also important to distinguish between the use of fear-based theories in the development of health risk messages about COVID-19 and the dissemination of unprofessional authored messages disseminated by social media. Therefore, the key issue that could affect health professionals' efforts to control COVID-19 infection is to counteract the spread of inaccurate and unnecessary information worldwide [4]. In addition to taking urgent steps to cut the transmission chain and provide public health services to tackle this outbreak, health systems must also take the necessary measures to tackle fears circulating on social media. Obviously, governments must also help people by adopting compensatory economic policies and providing financial support, especially to the populations who are faced with economic problems. To counter the spread of large amounts of inaccurate information, the health education bureau of states Ministries and health education Professionals must quickly take appropriate, useful, and necessary measures to control public rumors, misconceptions, false beliefs and inappropriate behaviors surrounding COVID-19 [5]. They also put an end to the rumors and concerns about the spread of Coronavirus worldwide by creating an interactive dashboard, so, public health professionals can rapidly reduce misinformation through appropriate and well-designed health information [1]. The bureau of health education of Ministry of health in all countries can also, in partnership with social media such as the World Health Organization, utilize social media's capacity to disseminate health information that helps break the transmission chain of COVID-19. According to the letter of the Iranian Health Education Scientific Association dated February 25, 2020, the Minister of Health has been advised that, given the prevalence of COVID-19, the largest responsibility of the COVID-19's National committee and Ministry of Health is transparency, accountability and community outreach to the needed information alongside community awareness and promoting the patterns of preventive behaviors and skills of self-care against COVID-19. This statement also stated that the Iranian Ministry of Health is expected to step in with the support of the formation of committee on health education and promotion , to provide accurate information at all levels , to provide evidence-based information about COVID-19 outbreak, and finally to develop appropriate interventions as the National health priority [6]. In fact, in the present situation, where we have not another choice except than non-pharmacological interventions such as quarantine and social distancing, we must use social media information to reinforce the information needed by the community to follow these procedures. Staying at home, public quarantine, being self-protect not only stop the COVID-19 transmission but also will prevent the transmission of false and unnecessary information. In principle, only by working with communities and citizens and providing accurate guidance and information from credible channels for public participation we can ensure about the effectiveness of interventions, especially quarantine and social distancing, against COVID-19. AS a result, striving to empower people and having informed people who can decide and act from a more informed and confident situation requires the provision of sound and coherent information from the health system and more importantly, to gain public trust.